Interdisciplinary case of multiple congenitally missing permanent teeth. (Bangladesh Journal of Medical Science, 2017)
Background: Patients presenting with congenitally missing teeth are relatively common and the aim of the dental team is to create a functional, healthy, and aesthetically acceptable dentition. The consequences of missing teeth include an abnormal occlusion or an altered facial appearance which may lead to psychological distress in some patients.Methods: The present case report describes a 23 year old patient with non-syndromic, congenitally missing permanent teeth (CMMPT). Clinical and radiographic examinations revealed agenesis of eight permanent teeth including the third molars. Following interdisciplinary treatment planning, the patient was treated with mechano therapy to correct a class III incisal relationship by space closure in the lower arch. In the upper arch, the right canine was substituted for a missing lateral incisor and space was opened for a prosthetic left lateral incisor (a mini implant).Results: Active orthodontic treatment was completed in 19 months. The management of CMMPT requires an interdisciplinary approach to achieve improved occlusal function and aesthetics.Conclusion: A combined orthodontic-implant-prosthodontic treatment approach can achieve an improved functioning occlusion, and favorable aesthetics.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.467-473